2017
DOI: 10.5045/br.2017.52.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, treatment, and outcome of primary rectal lymphoma: a single center experience of 16 patients

Abstract: BackgroundThe rectum is a relatively uncommon site for lymphoma compared with other gastrointestinal sites; no consensus regarding management of primary rectal lymphoma (PRL) has been formed due to its limited frequency. We aimed to investigate clinical characteristics and treatment outcomes in patients with PRL in a single center patient cohort.MethodsWe retrospectively analyzed the results of 16 consecutive patients with PRL, identified and treated at the Asan Medical Center, Seoul, Korea between January 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
5
0
2
Order By: Relevance
“…In our case, it was an early stage (IE) disease, and we did a wide staging and management plan prior to treatment, which contributed to good outcome with a progression-free survival so far of 30 months. Thus, malignant lymphoma of the rectum should be considered a different clinicopathological entity with different behavior and clinical presentation, and treatment should be defined based on this special clinical condition [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, it was an early stage (IE) disease, and we did a wide staging and management plan prior to treatment, which contributed to good outcome with a progression-free survival so far of 30 months. Thus, malignant lymphoma of the rectum should be considered a different clinicopathological entity with different behavior and clinical presentation, and treatment should be defined based on this special clinical condition [26].…”
Section: Resultsmentioning
confidence: 99%
“…In a single-center experience of 16 patients at Asan Medical Center, University of Ulsan College of Medicine, Seoul, Korea, a significant difference in survival between patients with early disease, stages I through II, compared with those with late disease, stage IV, was observed. The authors assumed that stage is a good predictor of survival in primary rectal lymphoma [26].…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, colorectal MALTomas have their own features. Many clinical retrospective studies have indicated that most colorectal MALTomas could be classified as Lugano stage I and II, which are considered of lower malignancy and more slowly progressive[ 3 , 10 ]. Meanwhile, it has been indicated that the long-range outcome exhibits no significant difference between the patients who received monotherapy and those who received combined therapy (surgery or radiation)[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment alternatives, there is no consensus on the best therapeutic strategy, with the options being: surgery, chemotherapy and radiotherapy, either as a single or combined treatment. 14,[32][33][34] In our patient, chemotherapy with an R-CHOP scheme was chosen, achieving criteria of complete remission after 6 cycles, without complications . In relation to the effect of chemotherapy on the evolution of IBD, different studies have shown its beneficial effect.…”
Section: Discussionmentioning
confidence: 99%